VD_FINDINFO HC / 2017 / 330 vom 13. April 2017 - VD Tribunal cantonal (2017)
DROIT DE CONSIGNER, MESURE PROVISIONNELLE, BAIL À FERME, DÉFAUT DE LA CHOSE | 261 al. 1 CPC (CH), 261 CPC (CH), 262 let. d CPC (CH)